Pontocerebellar Hypoplasia Maps to Chromosome 7q11.23: An Autopsy Case Report of a Novel Genetic Variant - Kritika Krishnamurthy; Amilcar A. Castellano-Sanchez; Christopher A. Febres-Aldana; Jyotsna Kochiyil; Carole Brathwaite; Robert J. Poppiti (Hindawi Limited, 2019)
Pontocerebellar hypoplasias are a group of autosomal recessive neurodevelopmetal disorders with varied phenotypic presentations and extensive genetic mutational landscape that are currently classified into ten subtypes. This classification is based predominantly on the genetic iterations as the phenotypic presentations are often broad and overlapping. Pontocerebellar hypoplasia type-3 (PCH3) is an autosomal recessive disorder characterized by a small cerebellar vermis, hyperreflexia, and seizures, described in Middle Eastern families in association with a homozygous truncating mutation of the PCLO gene in locus 7q11-21. This is a case of PCH, with previously unreported novel genetic alterations. The patient is a 1-week-old girl, born at term to a 26-year-old G4P0A3 woman in a nonconsanguinous relation. At birth, the baby was depressed and hypertonic with abnormal tonic-clonic movements of extremities. MRI revealed cerebellar and brainstem hypoplasia. Postmortem examination revealed a palmar simian crease. The cerebellum measured 2.5 cm from side to side and 1 cm from rostral to caudal. The vermis was rudimentary. Sectioning revealed a flattened linear fourth ventricle, scant abortive cerebellar foliae, and a markedly small cerebellum when compared with the cerebrum and with age-matched size. H&E-stained sections of cerebellum revealed scant rudimentary foliae. A rudimentary unilateral embolliform nucleus was identified. The remaining cerebellar nuclei were absent. Chromosomal microarray showed an interstitial duplication of 841 kB on chromosome 7q11.23. Locus 7q11.23 contains FGL2 and GSAP genes and is 5 MB upstream of the 7q11-21 region, suggesting a possible linkage. This novel genomic finding possibly represents a new familial variant of PCH closely associated with PCH-3 and further strengthens its association with the 7q11 locus.